Substrate Specificity of the RND-Type Multidrug Efflux Pumps AcrB and AcrD of Escherichia coli Is Determined Predominately by Two Large Periplasmic Loops - Elkins, Christopher A. (American Society for Microbiology, 2002)
AcrAB-TolC is a constitutively expressed, tripartite efflux transporter complex that functions as the primary resistance mechanism to lipophilic drugs, dyes, detergents, and bile acids in Escherichia coli. TolC is an outer membrane channel, and AcrA is an elongated lipoprotein that is hypothesized to span the periplasm and coordinate efflux of such substrates by AcrB and TolC. AcrD is an efflux transporter of E. coli that provides resistance to aminoglycosides as well as to a limited range of amphiphilic agents, such as bile acids, novobiocin, and fusidic acid. AcrB and AcrD belong to the resistance nodulation division superfamily and share a similar topology, which includes a pair of large periplasmic loops containing more than 300 amino acid residues each. We used this knowledge to test several plasmid-encoded chimeric constructs of acrD and acrB for substrate specificity in a marR1 ΔacrB ΔacrD host. AcrD chimeras were constructed in which the large, periplasmic loops between transmembrane domains 1 and 2 and 7 and 8 were replaced with the corresponding loops of AcrB. Such constructs provided resistance to AcrB substrates at levels similar to native AcrB. Conversely, AcrB chimeras containing both loops of AcrD conferred resistance only to the typical substrates of AcrD. These results cannot be explained by simply assuming that AcrD, not hitherto known to interact with AcrA, acquired this ability by the introduction of the loop regions of AcrB, because (i) both AcrD and AcrA were found, in this study, to be required for the efflux of amphiphilic substrates, and (ii) chemical cross-linking in intact cells efficiently produced complexes between AcrD and AcrA. Since AcrD can already interact with AcrA, the alterations in substrate range accompanying the exchange of loop regions can only mean that substrate recognition (and presumably binding) is determined largely by the two periplasmic loops.